Balance as a postural key component (core) for establishing physical state in school program reports - Mohammed Zerf; Mohamed Hadjar Kherfane (Nicolaus Copernicus University in Toruń, 2020)
Admit balance control tends to test muscle imbalances, mobility restrictions and postural-control stability problems. Specifically include in Euro fit Fitness Testing Battery and absent in FitnessGram. This cross section-study examined the importance of balancing test as a missing component (core) for establishing a physical state in school program reports. Build on Flamingo Balance test as a messing protocol requested in the FitnessGram battery test. To test this hypothesis, 400 male middle school students, age 13.03 ± 0.56-year, sector education Mostaganem for academic years 2017-2018 participate voluntaries in the present study. Classified into two groups based on their levels falls up or down to 5 in Flamingo Balance. Build on studying design, protocol and statistics applied. Our results claim balance as a key component functional fitness related to both lumbar and trunk muscular fitness strength endurance and flexibility. Recommend by this study as key assessing test motor fitness. Need to be integrated into FitnessGram to evaluate deficits in improvements postural-control related to muscular fatigue, which ultimately affects balance performance during ordinary tasks or complex dynamic activities.